Tinjauan Yuridis Tindak Pidana Penipuan dengan Cara Hipnotis Melalui Layanan Pesan Singkat Menurut Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Mokh Thoif; Rahayu Dwi Rossa (LAW Proscientist: Journal of Law Profesional Scientist, 2022)
The purpose of this research is to find out how the legal arrangements in Indonesia against criminal acts of fraud in cybercrime and what regulations are the basis for law enforcement officers in efforts to tackle fraud by hypnosis by using electronic devices. The research method used in the preparation of this thesis is a normative legal research method and the authors conclude that: 1. Online fraud has the same principles as conventional fraud. The only difference is the means of action, namely using Electronic Media (computers, internet, telecommunications equipment). The legal arrangements regarding this fraud crime are still limited to the use of the Criminal Code, and based on Law Number 11 of 2008 concerning Electronic Information and Transactions. 2. This criminal act of fraud can be charged under Article 378 of the Criminal Code as a criminal act of fraud or Article 28 paragraph (1) of the ITE Law on regulations regarding the spread of false and misleading news that harm consumers. Or it could be charged under both articles at once, namely, 378 KUHP in conjunction with Article 28 paragraph (1) in conjunction with Article 45 paragraph (1) of Law No. 11 of 2008 concerning fraud and or ITE crimes.